Characterizing dislocation loops in irradiated polycrystalline Zr alloys by X‐ray line profile analysis of powder diffraction patterns with satellites. Issue 3 (25th May 2021) - Ungár, Tamás; Ribárik, Gábor; Topping, Matthew; Jones, Rebecca M. A.; Dan Xu, Xiao; Hulse, Rory; Harte, Allan; Tichy, Géza; Race, Christopher P.; Frankel, Philipp; Preuss, Michael
Abstract : Satellites generated by small dislocation loops in polycrystalline proton‐ or neutron‐irradiated Zr alloys are characterized by X‐ray line profile analysis. The convolutional multiple whole‐profile procedure has been extended to characterize irradiation‐induced satellites around fundamental Bragg peaks. Abstract : This work extends the convolutional multiple whole profile (CMWP) line profile analysis (LPA) procedure to determine the total dislocation density and character of irradiation‐induced dislocation loops in commercial polycrystalline Zr specimens. Zr alloys are widely used in the nuclear industry as fuel cladding materials in which irradiation‐induced point defects evolve into dislocation loops. LPA has long been established as a powerful tool to determine the density and nature of lattice defects in plastically deformed materials. The CMWP LPA procedure is based on the Krivoglaz–Wilkens theory in which the dislocation structure is characterized by the total dislocation density ρ and the dislocation arrangement parameter M . In commercial Zr alloys irradiation‐induced dislocation loops broaden the peak profiles, mainly in the tail regions, and occasionally generate small satellites next to the Bragg peaks. In this work, two challenges in powder diffraction patterns of irradiated Zr alloys are solved: (i) determination of the M values from the long tail regions of peaks has been made unequivocal and (ii) satellites have been fitted separately, using physically well established principles, in order to exclude them from the dislocation determination process. Referring to the theory of heterogeneous dislocation distributions, determination of the total dislocation density from the main peaks free of satellites has been justified. The dislocation loop structure has been characterized by the total dislocation density of loops and the M parameter correlated to the dipole character of dislocation loops. The extended CMWP procedure is applied to determine the total dislocation density, the dipole character of dislocation loops, and the fractions of ⟨ a ⟩‐ and ⟨ c ⟩‐type loops in proton‐ or neutron‐irradiated polycrystalline Zr alloys used in the nuclear energy industry.